Establishing Law and Order After Conflict - Jones, Seth G. (RAND Corporation, 2005)
In a nation-building operation, outside states invest much of their resources in establishing and maintaining the host country's police, internal security forces, and justice system. This book examines post-Cold War reconstruction efforts, such as those in Iraq and Afghanistan, and assesses the success of U.S. and allied efforts in reconstructing internal security institutions.